Produção e caracterização de plantas aquáticas flutuantes livres cultivadas em efluente de tilápias - Cruz, Tatiane de Sousa (Universidade Federal do Tocantins, 2021)
Among the main species of aquatic herbaceous emerging from life free of interest for aquaculture, eight species with phytoremediation potential were identified: Pistia stratiotes, Eichornia crassipes, Salvinia molesta, Salvinia auriculata, Salvinia natans, Azolla pinnata, Azolla filiculoides e Spirodela intermedia. Specimens of these plants were grown in settling tanks of tilapia effluent solids, where they presented high dry mass productivity with an average of 4.25 MG MS ha-1 of water depth per year, high levels of phosphorus were recorded, with an average of 2.1 g kg-1 DM, and also bioextraction of this element of 98.4 kg MS ha-1 of water per year. Among these plants, three (S. molesta, A. pinnata and S. intermedia) were cultivated again in order to quantify productivity, nutrient extraction, and to quantify the content of macro-elements and chemical composition. S. Molesta showed higher productivity with 50.9 Mg ha-1 of water per year, and greater bioextraction of N: 205, P: 77 and K: 200 kg ha-1, while S. intermedia showed greater bioextraction of Ca: 309 and Mg: 136 g ha-1 of water per year. The herbaceous S. Molesta and A. pinnata had higher levels of energy and crude protein (4.000,00 cal g-1 DM; 33.6%), and higher stocks of nitrogen and phosphorus (5.55 and 2.22 g kg- 1 MS), while S. intermedia had higher stocks of potassium and magnesium (5.72 and 5.56 mg kg-1 DM), also of calcium (15.85 mg kg-1 DM).